Sonoelastography in differentiation between metastatic and tuberculous lymphadenitis - Renu Yadav; Amita Malik; Rajni Prasad (Journal of Head & Neck Physicians and Surgeons, 2022)
Introduction: The purpose of this study was to evaluate the diagnostic accuracy of sonography including Doppler and sonoelastography in differentiation between metastatic and tuberculous cervical lymphadenopathy. Materials and Methods: This single-center observational study was undertaken with 86 study subjects after defined inclusion and exclusion criteria as per study needs and imaging limitations. Sonographic and sonoelastographic examinations were done by two examiners, and the diagnosis was reached in consensus. Sonographic features assessed were size, short/long axis ratio, the presence or absence of echogenic hilum, and intranodal necrosis including pattern of vascularity. With ultrasonoelastography, color-coded elastograms and strain ratio (SR) were evaluated. Then, the accuracy of individual sonographic and sonoelastographic parameters as well as combined sonographic and sonoelastographic evaluation was evaluated against HPE diagnosis. Cutoff for all the combined evaluations was determined from receiver observing curve. Results: Out of 127 nodes examined, 100 were tuberculous and 27 were metastatic on histopathology. Among all ultrasound features, intranodal necrosis showed maximum sensitivity, i.e., 39% and specificity 96%. SR had highest sensitivity (95.6%) and specificity (96.3%) among all US and elastographic parameters. Conclusion: Sonoelastographic assessment has good diagnostic accuracy for differentiation between metastatic and tuberculous cervical lymphadenopathy and adds to sonographic assessment, thereby further increasing the diagnostic confidence.